Evaluation of implementation of logistics into Czech chemical industry in the period 1998-2003 - Vlčková, Vladimíra (Univerzita Pardubice, 2005)
Porgress in implementation of logistics into companies of chemical industry in the Czech Republic is presented using comparison of results of researches done it years 1998 and 2003. It was found that even after 5 years logistics fulfils mainly the service function. As the most significant positive change can be considered the fact that almost fourth part of tracked companies applied logistic management in contemporary conception and the range of activities managed and ensured by deparrtment of logistics was widening in 3/4 of moniitored companies. Informants see improvement of communication between particular departments, better information system and more knowledge about contemporary concept of logistics in company as most important possibilities how to accelerate enforcement of logistic management in the company.
Keywords: Logistika; logistický mamagement; chemický průmysl